2005
DOI: 10.1016/j.jas.2005.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Provenance analysis of Olivella biplicata shell beads from the California and Oregon Coast by stable isotope fingerprinting

Abstract: While Olivella beads are a common component of archaeological sites in California, and were widely traded in prehistory, no method has been developed to trace individual beads to a point of origin. This study examines the potential of stable carbon and oxygen isotopes to source Olivella beads from the Pacific coast. The study shows that 1) the oxygen isotopic composition of modern Olivella biplicata shells faithfully varies with ambient sea surface temperature and local upwelling, lending themselves to sourcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…This is because temperature is the primary environmental control on δ 18 O, and our previous work (Eerkens et al, 2005) showed that O. biplicata faithfully records a SST signal in its aragonitic shell. Sequential samples taken along growth lines of shells show seasonal patterns of increasing (springsummer) and decreasing (winter-spring) oscillations that track seasonal changes in SST.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…This is because temperature is the primary environmental control on δ 18 O, and our previous work (Eerkens et al, 2005) showed that O. biplicata faithfully records a SST signal in its aragonitic shell. Sequential samples taken along growth lines of shells show seasonal patterns of increasing (springsummer) and decreasing (winter-spring) oscillations that track seasonal changes in SST.…”
mentioning
confidence: 77%
“…Our previous research using oxygen and carbon stable isotope data (Eerkens et al, 2005(Eerkens et al, , 2007 sought to develop such a method for Olivella beads. Our approach takes advantage of the fact that ocean temperatures show a north-south gradient along the Pacific Coast, and that these temperatures affect the fractionation of oxygen isotopes in shell carbonate.…”
mentioning
confidence: 99%
“…O. biplicata is distributed along the coasts of California and Oregon, making the alignment of trade or exchange routes rather tricky. Eerkens et al (2005) showed that the d 18 O composition of a small sample of shell beads from central California pointed to a southern California origin for the shells. Subsequently, Eerkens et al (2010) reinforced this southern Californian focus using d 18 O, d 13 C and 87 Sr/ 86 Sr, although differences between various forms of shell beads showed that some were made in a range of locations and others in more restricted localities, suggesting some form of intra-regional specialization.…”
Section: Society and The California Olivella Shell Bead Production Anmentioning
confidence: 99%
“…Sourcing of Olivella shells may help to trace prehistoric and historical period shell bead exchange networks as well. Carbon isotope studies have proven to be effective in identifying Olivella sources based on general geographic locations (i.e., northern California and southern Ore-gon, Santa Barbara mainland and Santa Rosa Island, and Santa Cruz Island) (Eerkens et al 2005). Continued research has the potential to refine spatial resolution, perhaps to an island specific level.…”
Section: What Was the Nature Of Shell-bead Exchange In The Prehistorimentioning
confidence: 99%